Opini Masyarakat Tobasa Terhadap Kinerja Pemda Tobasa - Daniel J. Siahaan (Dinamika Politik, 2012)
This study is the study of Tobasa public opinion on the performance of Tobasa government. Focus discusses about how Tobasa public opinion on the performance of Tobasa government. The findings in this study includes there are six areas show that Tobasa local government performance still low. First, undeveloped education; Second, the healt sector has not advanced; Third, infrastructure development has not running; Fourth, people’s economy is still low; Fifth, natural resources untapped; Sixth, the government has not been going well . Method used is descriptive-quantitative that intended to describe an event in more detail.Keywords: performance, public opinion, leadership.